The Important Role of Audit Evidence in Ensuring the Fairness of Financial Statements - Purba, Restina; Sitanggang , Cindy Milasari Br; Simalango, Meylin Amanda (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study aims to analyze the essential role of audit evidence in ensuring the fairness and reliability of financial statements, particularly in detecting material misstatements and supporting auditors’ professional judgment. Methodology/approach: The research adopts a normative-descriptive approach using qualitative analysis. It involves a review of relevant literature, auditing standards (ISA and SPAP), and case studies on audit failures. Data sources include academic articles, audit guidelines, and financial reporting frameworks to evaluate how audit evidence contributes to achieving audit objectives. Results/findings: The study finds that sufficient and appropriate audit evidence is critical in forming audit opinions and detecting irregularities or fraud. Various types of evidence—physical, documentary, analytical, and testimonial—must be evaluated for relevance and reliability. The effectiveness of audit procedures depends on the auditor’s competence, independence, and adherence to professional standards. Conclusion: Audit evidence plays a pivotal role in maintaining the credibility of financial reporting. However, the absence of a structured evaluation of evidence or reliance on weak sources can lead to audit failure. Strengthening audit documentation, improving audit planning, and implementing risk-based approaches are key to enhancing audit quality. Limitations: This study is limited to secondary data and theoretical analysis without empirical testing or interviews with audit practitioners, which may affect the applicability of conclusions in real-world settings. Contribution: This paper contributes to audit research by reinforcing the theoretical foundation of audit evidence and providing practical insights into improving audit effectiveness and the reliability of financial statements.